Selection of Aptamers for Use as Molecular Probes in AFM Detection of Proteins - Maria O. Ershova; Amir Taldaev; Petr V. Konarev; Georgy S. Peters; Anastasia A. Valueva; Irina A. Ivanova; Sergey V. Kraevsky; Andrey F. Kozlov; Vadim S. Ziborov; Yuri D. Ivanov; Alexander I. Archakov; Tatyana O. Pleshakova (Biomolecules, 2023)
Currently, there is great interest in the development of highly sensitive bioanalytical systems for diagnosing diseases at an early stage, when pathological biomarkers are present in biological fluids at low concentrations and there are no clinical manifestations. A promising direction is the use of molecular detectors―highly sensitive devices that detect signals from single biomacromolecules. A typical detector in this class is the atomic force microscope (AFM). The high sensitivity of an AFM-based bioanalysis system is determined by the size of the sensing element of an atomic force microscope―the cantilever―the radius of the curvature of which is comparable to that of a biomolecule. Biospecific molecular probe–target interactions are used to ensure detection system specificity. Antibodies, aptamers, synthetic antibodies, and peptides can be used as molecular probes. This study has demonstrated the possibility of using aptamers as molecular probes for AFM-based detection of the ovarian cancer biomarker CA125. Antigen detection in a nanomolar solution was carried out using AFM chips with immobilized aptamers, commercially available or synthesized based on sequences from open sources. Both aptamer types can be used for antigen detection, but the availability of sequence information enables additional modeling of the aptamer structure with allowance for modifications necessary for immobilization of the aptamer on an AFM chip surface. Information on the structure and oligomeric composition of aptamers in the solution was acquired by combining small-angle X-ray scattering and molecular modeling. Modeling enabled pre-selection, before the experimental stage, of aptamers for use as surface-immobilized molecular probes.